2019
DOI: 10.1097/mao.0000000000002337
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Tumor Growth in Vestibular Schwannoma: An Argument for Lifelong Surveillance

Abstract: Objective: Previous research has shown that tumor growth during observation of small-to-medium sized sporadic vestibular schwannomas (VSs) occurs almost exclusively within 3 to 5 years following diagnosis. This has led some to consider ending surveillance after this interval. This study seeks to characterize a cohort of patients with tumors that exhibited late growth. Study Design: Retrospective cohort study. Setting: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…22 A smaller proportion (4%-8%) may exhibit delayed growth up to 11 years after diagnosis. 23 These findings highlight the importance of early and long-term surveillance of tumor size, which must be considered prior to CI.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…22 A smaller proportion (4%-8%) may exhibit delayed growth up to 11 years after diagnosis. 23 These findings highlight the importance of early and long-term surveillance of tumor size, which must be considered prior to CI.…”
Section: Discussionmentioning
confidence: 90%
“…In a recent study, Lees et al showed that a majority of VS tumors demonstrate early growth (68%) within the first years of diagnosis, defined as at least a 20% increase in size on volumetric analysis 22 . A smaller proportion (4%‐8%) may exhibit delayed growth up to 11 years after diagnosis 23 . These findings highlight the importance of early and long‐term surveillance of tumor size, which must be considered prior to CI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, we still recommend lifelong surveillance as 7.8% of our cases started to grow after 5 years. Prolonged surveillance has also been recommended by other investigators based on similar findings (10,11,21–24).…”
Section: Discussionmentioning
confidence: 93%
“…Tumor control rate (stable or decreased size) is 91%, while approximately 9% of the tumors are radioresistant; some tumors continue to grow despite high doses of radiation 45 . All this suggests that unlike malignant tumors, VS are particularly radioresistant, so clinical surveillance is required indefinitely in irradiated VS 46 . This relative resistance to radiation is not surprising given the low proliferative capacity of VS cells reflected in the slow clinical growth rate of VSs.…”
Section: Vestibular Schwannoma Radiobiologymentioning
confidence: 99%